(untitled) (Bulletin of criminological association of Ukraine, 2023)
Attention is drawn to the fact that the legislator did not formulate single features by which types of control activities in the field of urban development should be classified. Therefore, it is emphasized that the classification of the latter is most correctly carried out taking into account the legal status of the subjects of their implementation. This allows us to address not only the theoretical differences of each type of control, but also to see the diversity of the methodology used within each of them. It is concluded that control in the field of urban development activities in Ukraine in modern legal realities includes the following types: 1) state control, which is divided into subspecies: a) state architectural and construction control; b) licensing control; c) control in the field of cultural heritage protection; 2) public control, which is expressed in public discussion of draft urban development documentation at the local level and draft comprehensive restoration programs, as well as the activities of the Public Council under the Ministry of Community and Territorial Development of Ukraine; 3) self-control of subjects of construction activities.